Ignited by the Qur’an: Paludan’s Attempt to Produce Global Injustice Symbols at the Freedom of Expression/Blasphemy Nexus - Kühle, Lene (Temenos - Nordic Journal for the Study of Religion, 2024)
The Danish lawyer and politician Rasmus Paludan has gained notoriety for filming and uploading footage of demonstrations and burning copies of the Qur’an, first in 2019 in Denmark and later in Sweden. Based on videos and material from social and conventional media, this article investigates the background and political and legal opportunity structures of Paludan’s activism. It argues that Paludan’s actions are situated in reference to broader debates on freedom of expression in general and understanding of blasphemy in particular. Paludan’s treatment of the Qur’an resembles a global injustice symbol (Olesen 2015; 2016). The symbol becomes global in nature when it resonates cross-nationally and cross-culturally. In 2023, as the symbol spread to the global public sphere, the Danish government decided to introduce a blasphemy clause that had been repealed five years previously. This underlines Sherwood’s argument that blasphemy has made a paradoxical return as a contested global category in the twenty-first century.